Significance of Serum Pepsinogens in Atrophic Gastritis - Al-Hadithi, Hayfaa S.; Al-Derzi, Aida R.; Al-Ani, Muhammed M. (Journal of the Faculty of Medicine Baghdad, 2007)
Background: Chronic atrophic gastritis is a precancerous lesion. A commonly used test for the diagnosis of chronic atrophic gastritis, gastric endoscopy with biopsy collection, and a goodserological test would be best include low levels of pepsinogen I (PGI) or a low PGI/PGII ratio. Aim of the study: T o confirm the use of serum pepsinogens as a screening marker in atrophic gastritis.Patients and Methods: A study was conducted in the period between December 2005 and March 2006 on 25 patients with atrophic gastritis attending Gastroenterology and Hepatology Teaching Hospital in Baghdad, and 25 healthy control subjects. Sera were tested for PGI and PGII by ELISA test.Results and Conclusions: the serum PGI were decreased significantly with atrophic gastritis and the PGI/PGII ratio were decreased in (78%) of patient group and not affected in healthy people.